Students' Mental Behavior in Solving Mathematical Problems Based on Mathematical Ability and High Cognitive Style - Bambang, Raden Mas; Usman, Usman; Saiman, Saiman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Mental behavior is the activities that occur in a person's mind when solving mathematical problems. These activities are important to explore in problem solving, but exploration of activities is still rarely done by lecturers. This study aims to describe mental activities in solving mathematical problems of students who have high mathematical abilities and field independent (FI) and field dependent (FD) cognitive styles. This study uses a descriptive qualitative method with the subjects of the study being mathematics education students at Syiah Kuala University in the 2023 academic year. Data collection techniques were carried out using problem-solving tests and interviews. Data analysis was carried out by data reduction, presentation, and drawing conclusions. Data validity was carried out by time triangulation. The results of the analysis obtained mental activities in problem solving displayed by students with high mathematical abilities and FI cognitive styles were more complete than students with FD cognitive styles in the activities of reading questions, understanding questions, linking information and explaining solutions, but the mental activities displayed by FI were the same as FD at the calculation and manipulation stages. Therefore, it is necessary to provide experience to FD students to